Study of Chromium Containing Oxidants for Oxidation of Organic Compounds - Sapkota, Kamal Raj; Kumar, Arun (Kalika Journal of Multidisciplinary Studies, 2025)
Studies on redox behavior of inorganic and organic substrates is an important area of research. Potassium dichromate (K2Cr2O7), the orange crystalline solid is an excellent oxidant for inorganic substrates. Nevertheless, this issue arises with organic substrates because of their inadequate solubility in organic solvents, prompting efforts to substitute the K+ cation with alternative cations. A range of onium ions has been used to design several Cr(VI) oxidants, with di-tertiary butyl chromate (TBC) being the key oxidant utilized in this study.